Coexistence of blaOXA-58 and tet(X) on a Novel Plasmid in Acinetobacter sp. From Pig in Shanghai, China - Wang, Jing; Wang, Yan; Wu, Han; Wang, Zhen-Yu; Shen, Peng-Cheng; Tian, Yu-Qi; Sun, Fan; Pan, Zhi-Ming; Jiao, Xinan (Frontiers in Microbiology, 2020)
The purpose of this study was to characterize the complete sequence of a novel plasmid carrying tigecycline resistance gene tet(X) and carbapenemase gene blaOXA-58 from a swine Acinetobacter sp. strain SH19PTT10. Minimal inhibitory concentration was performed using microbroth dilution method. The isolate SH19PTT10 was highly resistant (16 mg/L) to tigecycline, and also exhibited resistance to ampicillin, streptomycin, tetracycline, chloramphenicol, florfenicol, ciprofloxacin and sulfamethoxazole/trimethoprim. Although SH19PTT10 harboured blaOXA-58, it was susceptible to cefotaxime and meropenem. The genome sequence of SH19PTT10 was determined using PacBio single-molecule real-time sequencing. Plasmid pYUSHP10-1 had a size of 174,032 bp, and showed partial homology to several plasmids found in Acinetobacter isolates. It contained two repA genes, putative toxin-antitoxin systems (HipA/HipB, RelE/RelB, BrnT/BrnA), partitioning genes (parA and parB), and heavy metal resistance-associated genes (copA/copB, nrp, czcA/czcD), but the transfer region or proteins was not found. pYUSHP10-1 carried 16 resistance genes, mainly clustered in two mosaic multiresistance regions (MRRs). The first MRR contained sul3, qacI-aadA1-clmA1-aadA2-blaCARB-2-dfrA16 cassette, aac(3)-IId and blaOXA-58. The blaOXA-58 gene was associated with ISAba3 as previously described. The second MRR is the tet(X) region (ISAcsp12-aph(3’)-Ia-IS26-ΔxerD-tet(X)-res-ISCR2-sul2) related to the corresponding region in other tet(X)-bearing plasmids. The pdif sites, as well as mobile elements, play an important role in mobilization of DNA modules and plasmid evolution. Coexistence of numerous resistance genes on a single plasmid may contribute to the dissemination of these genes under pressure posed by different agents, which may explain the presence of clinically crucial resistance genes tet(X) and blaOXA-58 in livestocks. Thus, rational drug use and continued surveillance of tet(X) and blaOXA-58 in livestocks are warranted.